Conhecimentos científicos e pedagógicos (PCK) em equilíbrio químico e pilhas expressos por professores de química da rede estadual em Cuiabá-MT - Floriano, Léo da Silva (2024)
This doctoral research is part of qualitative studies aimed at deepening the understanding of the scientific and pedagogical content knowledge of Chemistry teachers, both in initial training and in professional practice. In this context, I present the research question: How are the scientific and pedagogical knowledge in Chemical Equilibrium and Daniell Cells configured and expressed in the teaching practices of Chemistry teachers from the State Department of Education of Mato Grosso (SEDUC/MT) in the municipality of Cuiabá, as they describe their teaching in Basic Education? I adopt Narrative Inquiry as the research method, as the principles of this methodology allow for the systematization of teachers' experiences in educational contexts and the establishment of relationships between their knowledge regarding the processes of production and application of these constructed knowledge. This research involves four Chemistry teachers from the state education system of Mato Grosso (SEDUC/MT) who entered through a public exam in 2018 and are currently teaching Chemistry in Basic Education, assigned to second-year high school classes in Cuiabá. Regarding the research question, I chose the following investigative tools: questionnaires to characterize the participants and interviews to collect their narratives. To analyze the field texts and produce the research texts, I employ narrative methodology and the approach of discursive textual analysis (DTA), which is a qualitative data analysis methodology aimed at producing new understandings of the investigated narratives. I argue that the foundation of scientific and pedagogical knowledge essential for teaching Chemistry can be significantly strengthened during initial training through participation in teaching and research initiation projects from the beginning of the course. This process is further enriched by continuing education in postgraduate programs and the development of experiential knowledge built through professional practice. These combined elements enhance the production of teaching knowledge and promote innovative pedagogical practices, aiming to foster a science education that promotes citizenship. Through the results of this thesis, I seek to inspire ideas for the development of public policies in teacher education, highlighting the interaction between pedagogical and scientific knowledge is fundamental to educational practice. The results indicate that significant interactions between knowledge and teaching knowledge contribute to a more integrated and effective training, promoting a model that combines theory and practice. Additionally, I believe that a dialectical approach between scientific and pedagogical knowledge can significantly strengthen the formation and constitution of teachers' knowledge, positively reflecting on teaching performance in Mato Grosso and throughout the country. This integration not only enriches teaching practice but also prepares educators for contemporary challenges, aligned with an education that meets the needs of students and society.